1996
DOI: 10.1107/s0108767396093336
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of an all-RNA hammerhead ribozyme

Abstract: The conforn1ational features of an RNA A-fonn duplex with single adenosine bulges in two crystal structures will be discussed. Bulged nucleotides are frequent secondary structure motifs in RNA molecules and are often involved in Rl"\fA-RNA and Rl"\fA-protein interactions. RNA can be efficiently and selectively cleaved at bulge sites in the presence of divalent metal cations. The bulged As are looped-out, kink the duplex into the minor groove, and cause a marked opening of the normally cavernous Rl"\!A major .g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 0 publications
1
49
0
Order By: Relevance
“…Summary of metal-binding sites in the catalytic core of the hammerhead ribozyme+ The sequence, secondary structure, and numbering scheme for hammerhead ribozyme studied here are shown+ The 34-nt ribozyme was synthesized by in vitro transcription with T7 RNA polymerase as described (Milligan et al+, 1987;Nikonowicz et al+, 1992), and the 13-nt noncleavable substrate was chemically synthesized as described (Wincott & Usman, 1997)+ Potential Mg 2ϩ -binding sites identified by phosphorothioate studies are marked with an open circle, the A 13 site identified here is marked by a filled circle, sites observed by X-ray crystallography are marked with an X (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996Feig et al+, 1998), the uranyl photocleavage site (Bassi et al+, 1995) is marked with an asterisk, and the cleavage site is marked by an arrow+ The substrate used in this study has a dA at position 17 to prevent cleavage+ The shaded area indicates the so-called domain 2 in the hammerhead (Pley et al+, 1994) that contains the tandem G•A base pairs+ The dashed lines indicates formation of the sheared G•A base pairs+ FIGURE 2. 31 P NMR spectra of the hammerhead-substrate complex as a function of added MnCl 2 + The A 13 resonance is highlighted with an arrow, and the sharp peak at ;0+72 ppm is from inorganic phosphate that arises from hydrolysis of the 59-terminal triphosphate on the ribozyme+ The sample conditions are ;0+8 mM hammerhead ribozyme:substrate complex, 100 mM NaCl, 25 mM sodium succinate, 0+05% NaN 3 , 20% D 2 O, pH 5+5, 25 8C, and the Mn 2ϩ concentration was increased by the addition of aliquots of 0+55 mM MnCl 2 + The spectra were acquired on a Varian VXR-500 MHz spectrometer using proton decoupling during the 0+55-s acquisition time and with a sweep width of 30,000 Hz, a 1+0-s recycle delay, and 40,000 scans+ The NMR data were processed using Felix95 (MSI, Inc+) applying a 2-Hz exponential linebroadening window prior to Fourier transformation+ The spectra were scaled to the most upfield resonance and referenced externally to DSS+ experiments (;0+85 mM), the free concentration of Mg 2ϩ does not equal the total Mg 2ϩ ion concentration (as can generally be assumed in biochemical experiments performed at much lower RNA concentrations)+ Thus extensive dialysis of the hammerhead sample at each data point is required to achieve a known concentration of free Mg 2ϩ ion, which is then used in determining metal-binding affinities by NMR+ The effects of free Mg 2ϩ concentration on this site are depicted in Figure 3, where the A 13 31 P resonance shifts and broadens as a function of Mg 2ϩ concentration+ The broadening of the A 13 resonance indicates that it is undergoing chemical exchange on the NMR chemical shift timescale between the metal-free and metal-bound states (Gutowsky & Holm, 1956;Lian & Roberts, 1993)+ The equilibrium constant for metal binding can be determined from lineshape analysis using the chemical shifts of the free and bound states and the lifetime for exchange, assuming a single metal binding to this site …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary of metal-binding sites in the catalytic core of the hammerhead ribozyme+ The sequence, secondary structure, and numbering scheme for hammerhead ribozyme studied here are shown+ The 34-nt ribozyme was synthesized by in vitro transcription with T7 RNA polymerase as described (Milligan et al+, 1987;Nikonowicz et al+, 1992), and the 13-nt noncleavable substrate was chemically synthesized as described (Wincott & Usman, 1997)+ Potential Mg 2ϩ -binding sites identified by phosphorothioate studies are marked with an open circle, the A 13 site identified here is marked by a filled circle, sites observed by X-ray crystallography are marked with an X (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996Feig et al+, 1998), the uranyl photocleavage site (Bassi et al+, 1995) is marked with an asterisk, and the cleavage site is marked by an arrow+ The substrate used in this study has a dA at position 17 to prevent cleavage+ The shaded area indicates the so-called domain 2 in the hammerhead (Pley et al+, 1994) that contains the tandem G•A base pairs+ The dashed lines indicates formation of the sheared G•A base pairs+ FIGURE 2. 31 P NMR spectra of the hammerhead-substrate complex as a function of added MnCl 2 + The A 13 resonance is highlighted with an arrow, and the sharp peak at ;0+72 ppm is from inorganic phosphate that arises from hydrolysis of the 59-terminal triphosphate on the ribozyme+ The sample conditions are ;0+8 mM hammerhead ribozyme:substrate complex, 100 mM NaCl, 25 mM sodium succinate, 0+05% NaN 3 , 20% D 2 O, pH 5+5, 25 8C, and the Mn 2ϩ concentration was increased by the addition of aliquots of 0+55 mM MnCl 2 + The spectra were acquired on a Varian VXR-500 MHz spectrometer using proton decoupling during the 0+55-s acquisition time and with a sweep width of 30,000 Hz, a 1+0-s recycle delay, and 40,000 scans+ The NMR data were processed using Felix95 (MSI, Inc+) applying a 2-Hz exponential linebroadening window prior to Fourier transformation+ The spectra were scaled to the most upfield resonance and referenced externally to DSS+ experiments (;0+85 mM), the free concentration of Mg 2ϩ does not equal the total Mg 2ϩ ion concentration (as can generally be assumed in biochemical experiments performed at much lower RNA concentrations)+ Thus extensive dialysis of the hammerhead sample at each data point is required to achieve a known concentration of free Mg 2ϩ ion, which is then used in determining metal-binding affinities by NMR+ The effects of free Mg 2ϩ concentration on this site are depicted in Figure 3, where the A 13 31 P resonance shifts and broadens as a function of Mg 2ϩ concentration+ The broadening of the A 13 resonance indicates that it is undergoing chemical exchange on the NMR chemical shift timescale between the metal-free and metal-bound states (Gutowsky & Holm, 1956;Lian & Roberts, 1993)+ The equilibrium constant for metal binding can be determined from lineshape analysis using the chemical shifts of the free and bound states and the lifetime for exchange, assuming a single metal binding to this site …”
Section: Resultsmentioning
confidence: 99%
“…Divalent metal ions play key roles in the folding and function of RNA and are critical to catalytic activity of most ribozymes+ The global folding and catalytic activity of the hammerhead ribozyme is dramatically influenced by metal ion type and concentration (Dahm & Uhlenbeck, 1991;Koizumi & Ohtsuka, 1991;Dahm et al+, 1993;Bassi et al+, 1995Bassi et al+, , 1996Bassi et al+, , 1997, and highaffinity metal binding has been proposed to affect two conformational transitions in the hammerhead (Bassi et al+, 1996(Bassi et al+, , 1997)+ A number of specific metal-binding sites have been observed by biophysical, X-ray crystallographic, and biochemical techniques (see Fig+ 1) (Ruffner & Uhlenbeck, 1990;Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996Menger et al+, 1996;Knoll et al+, 1997;Feig et al+, 1998;Horton et al+, 1998;Murray et al+, 1998;Feig & Uhlenbeck, 1999)+ However, except for two examples involving unusual metal ions [the study of Cd 2ϩ binding to a modified hammerhead containing a single phosphorothioate (Peracchi et al+, 1997) and a Tb 3ϩ -binding site that was characterized biochemically and crystallographically (Feig et al+, 1998)], it has not been possible to obtain binding affinities for specific sites within the hammerhead ribozyme+ In the current study, 31 P NMR techniques have been used both to identify a novel metal-binding site associated with the A 13 phosphate in the catalytic core of the hammerhead ribozyme and to determine the Mg 2ϩ ion-binding affinity of this site+…”
Section: Introductionmentioning
confidence: 99%
“…A: Consensus secondary structure of the hammerhead numbered according to (Hertel et al+, 1992)+ The essential core nucleotides are designated in bold (H ϭ A, U, C and N ϭ nucleotide)+ The three loops (L1-L3) vary in length and sequence depending on where the hammerhead motif is embedded+ Arrow represents the site of cleavage 39 of position 17+ B: Three bimolecular formats of the hammerhead designated by the helices through which the substrate binds the ribozyme+ used+ Steps that have been proposed include: (1) conversion of E{S to a short-lived active complex with the attacking 29 oxygen positioned in line with the scissile phosphodiester bond (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996; (2) a large conformational rearrangement that involves docking of the two domains of the catalytic core (Peracchi et al+, 1997); (3) a metal ion binding step (Long et al+, 1995); or (4) a conformational switch from an inactive E{S to an active E{S (Bassi et al+, 1995(Bassi et al+, , 1996+ It is well known that many RNA sequences can adopt multiple alternate structures that are as stable as the native structure (Herschlag, 1995;Uhlenbeck, 1995)+ The addition of a single alternate equilibrium involving one of the species of the minimal hammerhead kinetic pathway can alter the kinetics of cleavage in several different ways+ Both the rate of exchange and the overall equilibrium between the native and alternate structure can significantly alter the kinetic properties of the cleavage reaction+ To give just one example, consider a situation in which an alternate conformation of E{S, termed [E{S]9, forms off of the main pathway (Fig+ 3A)+ If the exchange rate is slow relative to the rate constant for cleavage (k 2 ) and the equilibrium constant results in, say, 40% of the complex being [E{S]9, the cleavage reaction will be biphasic with a fast rate, k 2 , up to 60% product, followed by a slow rate reflecting the conversion of [E{S]9 to E{S+ Very different behavior exists when the exchange rate is fast with respect to k 2 + As before, the amount of active E{S available for conversion to E{P1{P2 is reduced by the fraction of [E{S]9 formed at equilibrium, however, a single, slower rate of cleavage will be observed that equals (k conf 9/k conf )k 2 + Many other possible scenarios involving alternate structures can exist (Fig+ 3B,C,D) and these species are not always easy to detect+ The challenge is therefore to uncover these additional steps and to kinetically distinguish them from the steps of the minimal kinetic pathway+ The easiest hammerheads to work with are obviously those that do not have alternate conformations of the reaction species+ Several of these kinetically well-behaved or ideal hammerheads have been identified and steps can be taken to test whether sequences show such behavior (Fedor & Uhlenbeck, 1990, 1992Heus et al+, 1990;Hertel et al+, 1994;Clouetd'Orval & Uhlenbeck, 1996)+ Kinetically w...…”
Section: The Hammerhead Kinetic Pathway-an Overviewmentioning
confidence: 99%
“…The hammerhead ribozyme is a small RNA motif that self cleaves at a specific phosphodiester bond to produce 29,39 cyclic phosphate and 59 hydroxyl termini (Hutchins et al+, 1986;Forster & Symons, 1987a)+ The secondary structure of the hammerhead consists of three helices of arbitrary sequence and length (designated I, II, and III) that intersect at 15 nucleotides termed the catalytic core (Fig+ 1A) (Forster & Symons, 1987b;Hertel et al+, 1992)+ The X-ray crystal structures of two hammerhead ribozyme-inhibitor complexes revealed that the core residues fold into two separate domains and the helices are arranged in a Y-shape conformation with helix I and helix II forming the upper portion of the Y (Pley et al+, 1994;Scott et al+, 1995)+ Although the hammerhead is found as an intramolecular motif embedded in several RNAs in vivo (Symons, 1989), it can be assembled from two separate oligonucleotides (Fig+ 1B) in three different arrangements (Uhlenbeck, 1987;Haseloff & Gerlach, 1988;Koizumi et al+, 1988;Jeffries & Symons, 1989)+ In these bimolecular formats, the hammerhead effects RNA cleavage in a similar manner to a true "enzyme," proceeding through multiple rounds of substrate binding, cleavage, and product release (Uhlenbeck, 1987)+ Because of its relatively small size, ease of synthesis, and its well-described structure and cleavage properties, the hammerhead has been useful for studying many facets of RNA structure and function+ The major focus has been on understanding the mechanism by which the hammerhead catalyzes RNA cleavage+ The role of specific functional groups in either binding or catalysis has been probed by incorporation of both natural and modified nucleotides into the core of the hammerhead (Bratty et al+, 1993;Tuschl et al+, 1995;McKay, 1996;Chartrand et al+, 1997)+ In addition, the importance of metal ions in mediating cleavage has been studied extensively with the aim of establishing their roles in folding and catalysis (Dahm & Uhlenbeck, 1991;Perreault et al+, 1991;Dahm et al+, 1993;Grasby et al+, 1993;Menger et al+, 1996;Peracchi et al+, 1997;Feig et al+, 1998)+ The hammerhead ribozyme has also been used for the calibration of methods to probe more general properties of RNA such as folding and dynamics+ These methods include a gel mobility shift assay (Bassi et al+, 1995...…”
Section: Introductionmentioning
confidence: 99%
“…Cryoenzymology is a tool for studying enzyme reaction mechanisms at low temperatures that has been used extensively on proteins (Makinen & Fink, 1977;Fink & Geeves, 1979;Douzou, 1983;Travers & Barman, 1995)+ The technique involves adding a cryoprotectant, often an organic solvent such as methanol, ethylene glycol, or DMSO, to prevent the enzyme solution from freezing and thereby allowing kinetic analysis at low temperature+ By extending the temperature range of the kinetic studies to well below 0 8C, intermediates along a reaction pathway may be observed that are otherwise undetectable+ When these intermediates have spectroscopic features, they can be observed directly, but their presence can also be inferred by changes in the kinetic behavior of the system+ For example, a change in the rate-determining step of the reaction at some low temperature might be observed+ This phenomenon often results in curved Eyring or Arrhenius plots, which derive from the intersection of the two lines, each representing a different elementary process of a composite rate constant (Travers & Barman, 1995)+ The hammerhead ribozyme is a small RNA that catalyzes a self-cleavage reaction (Fig+ 1) (McKay, 1996;Thomson et al+, 1996;Zhou & Taira, 1998)+ In vitro studies of this ribozyme generally employ two RNA fragments such that one can be considered the ribozyme and the other the substrate+ The standard kinetic scheme for these hammerheads involves substrate binding to form the enzyme-substrate complex (ES), cleavage of the phosphodiester bond, and product release (Fedor & Uhlenbeck, 1992;Hertel et al+, 1994)+ Whereas this scheme adequately describes the overall reaction, several laboratories have proposed that at least one additional, albeit kinetically unobserved, step must occur after substrate binding and prior to cleavage to form an active intermediate, ES9 (Fig+ 1B)+ Two reasons prompted these suggestions+ First, two independent X-ray crystal structures (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996 showed that the conformation around the cleavage site was inappropriate for in-line attack by the 29-OH group on the adjacent phosphodiester bond+ Second, a good deal of biochemical data was inconsistent with the crystal structure being close to an active conformation+ For example, substitution of the functional groups of G5 in domain I (Ruffner et al+, 1990;Tuschl et al+, 1993) and certain 29-OH (Williams et al+, 1992) and phosphate oxygens in domain II (Ruffner & Uhlenbeck, 1990;Peracchi et al+, 1997) completely abolish activity, but do not interact with other residues in the crystal structure+ Because preliminary NMR data suggest that the crystal structure closely reflect...…”
Section: Introductionmentioning
confidence: 99%